Identification of Trimyristine from Oil, Crystals, and Residue of Nutmeg (Myristica fragrans) in South Aceh (Indonesia) Using GC-MS - Bhayu Gita Bhermana; Sri Nengsih; Heri Hasmizal (agriTECH, 2023)
South Aceh Regency is the largest nutmeg-producing area in Aceh Province, Indonesia, but its potential for oil production has not been fully optimized. Nutmeg (Myristica fragrans) oil is one of the essential oil groups obtained from the distillation of the nutmeg plant, including its peel, mace, and seeds. One of the essential compounds found in nutmeg oil is trimyristin. Therefore, this research aimed to identify and determine the content of trimyristin in the oil, crystals, and residue of nutmeg seeds from South Aceh. It was carried out in stages wherein nutmeg oil distillation was performed by a simple distillation method. Trimyristin was separated from the oil using the reflux method and from the residue by the maceration method. The compound was obtained from the isolation of nutmeg oil using chloroform as a solvent. The oil was characterized based on SNI No. 06-2388 of 2006, then trimyristin was isolated and identified by Gas Chromatography-Mass Spectrophotometry (GC-MS). The results showed that the characterization of nutmeg oil did not fulfill the SNI . The color and smell tests were not in accordance with those of nutmeg oil, the specific gravity was 0.909, the refractive index was 1.63, and the solubility in alcohol was cloudy. Trimyristin of 11.23% was only found in the residue, but it was not detected in the oil and crystals.